Enhanced Targeting, Retention, and Penetration of Amphotericin B Through a Biomimetic Strategy to Treat Against Vulvovaginal Candidiasis (Adv. Therap. 1/2023). Issue 1 (18th January 2023) - Lin, Yijing; Yin, Qingqing; Zhuge, Deli; Hu, Yiqin; Yang, Xuewei; Tian, Dongyan; Li, Li; Wang, Haonan; Liu, Shuangshuang; Weng, Cuiye; Zhang, Xufei; Wen, Bin; et al.
Abstract : Amphotericin B (AmB) preloaded polymeric cores cloaked with vaginal epithelial cells membrane (VM‐ANP) are capable of localizing to the sites of Candida albicans infection. Upon such strong adhesion, retention, and penetration, VM‐ANP shows a controlled release of AmB; thus, enhancing the fungal killing to reach its full potential. This is reported by Mengchun Chen, Ledan Wang, Yijie Chen, and co‐workers in article number 2200086 .